PENGAKUAN PENDAPATAN DAN BEBAN KONTRAK PADA PERUSAHAAN JASA KONSTRUKSI (STUDI KASUS PADA PERUSAHAAN CV. TALITA JAYA BONDOWOSO) - Dwi Muharomawati; Yulinartati; Elok Fitriya (Juremi: Jurnal Riset Ekonomi, 2021)
Revenues and expenses are an important part of the financial statements. This research was conducted on CV. Talita Jaya Bondowoso. The purpose of this study is to analyze the application of the revenue and expense recognition method in construction service companies. This type of research is a type of qualitative descriptive research. The type of data used is secondary data, namely data obtained from the treasurer or the accounting department of the company, in the form of financial statements. The results showed that CV. Talita Jaya in determining the method of recognizing revenues and expenses has complied with PSAK No. 34 (revised 2014), but in determining the completed contract method it is not in accordance with PSAK No. 34 (revised 2014), where the company applies the percentage-of-completion method in recognizing revenues and expenses.